OPTIMALISASI BIMBINGAN DAN PENYULUHAN SATUAN NARKOBA DALAM RANGKA MENCEGAH PENYALAHGUNAAN NARKOBA PADA KALANGAN SWASTA DI POLRES PASURUAN - I PUTU PRATAMA YOGA Pratama (Advances in Police Science Research Journal, 2019)
This research is motivated by the continuing emergence of drug abuse crimes in Pasuruan Regency. Most of the perpetrators or victims of drug abuse crime come from the private employee. The private employee referred to in this research is a job or person who does work independently and is not determined by the boss because there is no boss for him. Thus, the most effective efforts are preventive measures to prevent drug abuse in the private employee. Therefore, a research was conducted which aims to determine the process of implementing guidance and counseling by the Narcotics Unit, to find out the Narcotics Unit efforts in optimizing guidance and counseling, and to determine the factors that can influence the optimization of guidance and counseling. This research was conducted with a qualitative approach, using the type of field research research, as well as data collection techniques by interview, observation, and document study. The results of the study found that the guidance and counseling activities carried out by the Narcotics Unit Polres Pasuruan were not optimal. This is because the management of guidance and counseling activities has not been maximized, such as the schedule of activities that are not right on target, a special team has not been formed to carry out activities, the intensity of activities is still lacking and there are still members who have not implemented vocational education. In addition, there are also several inhibiting factors in the implementation of guidance and counseling, namely human resources, facilities and infrastructure, budget, and legal awareness or the mindset of private employees. Based on the results of the study, the authors suggest additional personnel to be placed in the Narcotics Unit. In preparing the schedule for the implementation of guidance and counseling activities, to pay more attention to targets or targets, and Satresnarkoba are expected to be more active in providing guidance and counseling targeting the private employee. Not only waiting for requests. In addition, it is necessary to procure official inventory items needed in the implementation of guidance and counseling. Keywords: Guidance and Counseling, Narcotics Unit, Drug Prevention, Private employee.